The Effectiveness of Intravenous Magnesium Sulfate for Deliberate Hypotension in Rhinoplasty - Seyed Mohammad Mireskandari (Archives of Anesthesia and Critical Care, 2015)
Background: Deliberate hypotension is a strategy that reduces intraoperative bleeding and increases the speed of surgery in otolaryngology procedures. Magnesium (Mg) sulfate is a vasodilator agent that reduces intraoperative hypnotic requirements and in combination with analgesic agents, it reduces intraoperative and postoperative pain. In this study we evaluated the use of intravenous Mg sulfate for inducing deliberate hypotension in rhinoplasty. Methods: Sixty ASA I, II patients aged between 18 to 45, scheduled for rhinoplasty were recruited into a randomized clinical trial. Patients were randomly assigned into placebo (group P) and Mg sulfate (group M) groups. For patients in group M, 40m/kg Mg sulfate was administered before induction and continued with 15mg/kg/hr infusion during the operation. Patients of group P received normal saline as placebo. In each group mean arterial pressure (MAP), mean heart rate, amount of bleeding, anesthetic agents, opioid requirement and duration of surgery were recorded. The incidence of nausea, vomiting, shivering and the score of pain were recorded in post-operative period in both groups. Results: Patients in group M had lower MAP (P= 0.0001), less intraoperative bleeding (P=0.0001), lower anesthetic agents (P=0.0001) and opioid consumption (P=0.001), and shorter duration of procedure (P=0.0001). Mean heart rate was lower in group P (P=0.001). Moreover, surgeon`s satisfaction was more in group P (P=0.001).They also had less incidence of post-operative nausea and vomiting (P=0.008), shivering (P=0.001) and lower pain scores postoperatively (P=0.0001). Conclusion: Magnesium sulfate can be a useful drug to induce controlled hypotension in rhinoplasty surgery. By employing this agent patients have better anesthetic condition and recovery profile.